Development of Eco-Friendly Big Book Media to Increase Interest and Science Literacy of 1st Grade Students - Ika Sri Wulandari; Ikhlasul Ardi Nugroho; Garib Firman Buaga (Jurnal Penelitian Pendidikan IPA, 2025)
Interest in learning and science literacy needs to be developed early on through learning media that is interesting, interactive, contextual, and environmentally friendly to form student awareness in protecting the environment. This study is a research and development (R&D) of Eco-Friendly Big Book Media for grade 1 elementary school students, which aims to increase students' interest and science literacy. This media is prepared with an interactive and varied approach, in order to increase the involvement of students in the learning process. This research uses the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. However, this research was only carried out up to the validation stage for product feasibility testing, which involved qualitative and quantitative data analysis, focusing on validation by material experts and media experts as an evaluation step. The validation results show that the Eco-Friendly Big Book Media is very feasible to use, with a feasibility score of 96% from material experts and 95% from media experts. This media is expected to be an effective solution in supporting teachers to increase students' interest and science literacy, especially in grade 1 elementary school.